Tinjauan Hukum Islam Terhadap Praktik Penjualan Ikan Hasil Panen Melalui Perantara Di Kecamatan Glagah Kabupaten Lamongan - Dani El Qori (MASADIR: Jurnal Hukum Islam, 2021)
Buying and selling transactions are economic transactions that are mostly carried out by humans. This transaction continues to grow with the times. The development of buying and selling transactions necessitates the existence of appropriate and relevant legal instruments to regulate these transactions. Islamic law is believed to be a legal rule that is appropriate and relevant to be applied in all times and places. In its development, buying and selling not only confronts the seller and the buyer. Sometimes it takes a third party to act as an intermediary between the seller and the buyer. The practice of buying and selling in the presence of intermediaries is often carried out by fish pond owners in Glagah sub-district, Lamongan Regency. In this article, we will examine in depth the practice of selling fish through intermediaries from the perspective of Islamic law. The author uses the theory of buying and selling contracts, wakalah, ijarah, and samsarah in Islamic law. Kata Kunci : Buy and sell, intermediary, Islamic Law.